Trade union debates on sustainable development in Brazil and Argentina - Bruno Dobrusin (International Labour Organization (ILO), 2015)
This paper analyses the development strategies followed by the governments of Argentina and Brazil since the election of left-oriented parties (2002 in Brazil and 2003 in Argentina), and focuses on the role the trade union movement has had on their policies and how it challenged their growth strategies. The main argument is that both of these countries underwent significant socio-economic improvements since these governments were elected, but this development has mainly been based on their extractive industries, such as mining, forestry, transgenic agribusiness-based agriculture and oil. These activities have produced immense wealth, which these governments very effectively distributed focusing on the poorest sectors. This is the basis of the massive support that both the Lula (and later Rousseff) and the Kirchners' administrations consistently receive. However, the model of redistribution, still inadequate in several aspects, remains controversial as it is unsustainable in the medium- to long-term, and it has produced intense social dislocations in the populations directly affected. These contradictions and the trade union responses to it are a central focus throughout the essay.
Keywords: 330; sustainable development; trade union power; state intervention; green jobs; dual economy; commodity; petroleum resources; Argentina; Brazil